Financial regulation, governance, and stability : building an inclusive and resilient financial future - Yakubu, Ibrahim Nandom, 1989-; Kapusuzoglu, Ayhan; Ceylan, Nildag Basak (Routledge international studies in money and banking., 2026)
The COVID-19 pandemic significantly disrupted global financial systems, exposing vulnerabilities in regulatory frameworks and governance structures. As economies struggled to recover, it became clear that new approaches were needed to ensure stability and mitigate future risks. In addition, the crisis exacerbated existing inequalities, highlighting the need for more inclusive financial systems that can serve all segments of society, particularly vulnerable populations. This book critically examines the evolution of financial regulation and governance in response to the challenges posed by the pandemic. It provides an in-depth analysis of how governments, financial institutions, and policymakers adapted to the unprecedented crisis, identifying key regulatory shifts and policy responses that have shaped the current financial environment. It explores strategies for enhancing stability, improving market oversight, and ensuring equitable access to financial services. Further, it explores the role of RegTech, FinTech, and Central Bank Digital Currencies in enhancing regulatory efficiency and promoting financial inclusion. This book synthesizes research across disciplines and presents case studies that highlight both successes and shortcomings in the global response to financial instability. Additionally, it offers insights into future trends, with a focus on fostering resilient, inclusive, and sustainable financial systems worldwide and emphasizes the importance of adaptive regulatory frameworks and collaborative efforts among stakeholders to address ongoing challenges in the post-COVID financial landscape. This book is ideal for a broad audience, including policymakers, researchers, and financial industry professionals, as well as those interested in understanding the intersection of financial regulation, governance, and social equity in a post-pandemic world.